2003
DOI: 10.1177/08830738030180011301
|View full text |Cite
|
Sign up to set email alerts
|

Schilder's Disease: Case Study With Serial Neuroimaging

Abstract: Schilder's myelinoclastic diffuse sclerosis is a rare sporadic demyelinating disease that usually affects children between 5 and 14 years old. The disease often mimics intracranial neoplasm or abscess. We report a 9-year-old girl with Schilder's disease who presented with left hemiparesis. Cranial computed tomography and magnetic resonance imaging (MRI) showed large lesions in the subcortical white matter of the occipital and parietal lobes of both hemispheres that were indistinguishable from an abscess. A cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…1 Because of its atypical presentations, Schilder disease often poses a diagnostic challenge. [2][3][4] Its course can be monophasic or relapsing, which is difficult to predict at the outset of the disease. Therefore, whether and when disease-modifying therapy (DMT) is helpful remains to be investigated.…”
mentioning
confidence: 99%
“…1 Because of its atypical presentations, Schilder disease often poses a diagnostic challenge. [2][3][4] Its course can be monophasic or relapsing, which is difficult to predict at the outset of the disease. Therefore, whether and when disease-modifying therapy (DMT) is helpful remains to be investigated.…”
mentioning
confidence: 99%
“…Mehler and Rabinowich [5] described a 12-year-old girl with bifrontal lesions involving the anterior corpus callosum. Kurul et al [8] reported a 9-year-old girl with lesions in bilateral parieto-occipital subcortical areas and genu and splenium of the corpus callosum. However, the pattern of extension to the corpus callosum seems to vary in each case.…”
Section: Discussionmentioning
confidence: 99%
“…Классическая болезнь Шильдера (периаксиальный диффузный лейкоэнцефалит) встречается крайне редко, в литературе описано 10 случаев заболевания, которые удовлетворяют диагностическим критериям [8]. Заболевание дебютирует в детском и молодом возрасте и клинически характеризуется острой психиатрической симптоматикой, внутричерепной гипертензией, интеллектуально-мнестическими нарушениями, двигательными нарушениями в виде геми-или тетрапарезов, дизартрией и дисфагией, уни-или билатеральной оптической нейропатией, гомонимной гемианопсией, прогрессивным ухудшением без повышения температуры [9].…”
Section: очаги в двиunclassified